Intraoperative three-dimensional fluoroscopy after transpedicular positioning of Kirschner-wire versus conventional intraoperative biplanar fluoroscopic control: A retrospective study of 345 patients and 1880 pedicle screws - Kerry, Ghassan (Medknow Publications & Media Pvt Ltd, 2014)
STUDY DESIGN: Retrospective study. OBJECTIVE: The aim was to find out whether intraoperative three-dimensional imaging after transpedicular positioning of Kirschner wire (K-wire) in lumbar and thoracic posterior instrumentation procedures is of benefit to the patients and if this technique is accurately enough to make a postoperative screw position control through computer tomography (CT) dispensable. PATIENTS AND METHODS: Lumbar and thoracic posterior instrumentation procedures conducted at our department between 2002 and 2012 were retrospectively reviewed. The patients were divided into two groups: group A, including patients who underwent intraoperative three-dimensional scan after transpedicular positioning of the K-wire and group B, including patients who underwent only intraoperative biplanar fluoroscopy. An early postoperative CT of the instrumented section was done in all cases to assess the screw position. The rate of immediate intraoperative correction of the K-wires in cases of mal-positioning, as well as the rate of postoperative screw revisions, was measured. RESULTS: In general, 345 patients (1880 screws) were reviewed and divided into two groups; group A with 225 patients (1218 screws) and group B with 120 patients (662 screws). One patient (0.44%) (one screw [0.082%]) of group A underwent postoperative screw correction while screw revisions were necessary in 14 patients (11.7%) (28 screws [4.2%]) of group B. Twenty-three patients (10.2%) (28 K-wires [2.3%]) of group A underwent intraoperative correction due to primary intraoperative detected K-wire mal-position. None of the corrected K-wires resulted in a corresponding neurological deficit. CONCLUSION: Three-dimensional imaging after transpedicular K-wire positioning leads to solid intraoperative identification of misplaced K-wires prior to screw placement and reduces screw revision rates compared with conventional fluoroscopic control. When no clinical deterioration emerges, a postoperative CT seems to be dispensable using this intraoperative three-dimensional control method.